Integrasi Ekonomi Biru dalam Penganggaran Daerah Sulawesi Utara: Analisis Manajemen Keuangan Publik Berbasis Blue Finance - Junior Lakat; Tri Oldy Rotinsulu; Anderson Guntur Kumenaung; Victor Paskah Kalawat Lengkong; Hendrik Gamaliel (Universitas Negeri Padang, 2025)
This study aims to examine the gap between the performance of the marine and fisheries sector and subnational fiscal capacity, and to formulate an institutional framework for integrating blue finance instruments into the provincial budgeting system (APBD) of North Sulawesi. An explanatory sequential mixed‑methods design was employed. The quantitative phase applied descriptive analysis and simple linear regression to time‑series data (2021–2025) from Statistics Indonesia and fiscal reports to assess the relationship between fisheries exports, sectoral GDP, and local own‑source revenue. The qualitative phase used thematic analysis of regional development plans, fiscal policy documents, and academic literature on sustainable finance to identify regulatory, institutional, and financial constraints. The results reveal a development paradox: although fisheries exports grew rapidly (CAGR ≈ 10.4% during 2021–2024) and showed a strong positive correlation with sectoral GDP, this growth did not translate into higher fiscal autonomy, as more than 60.48% of regional revenue still originated from central government transfers. Based on these findings, the study proposes a Blue Economy Financing Framework that combines marine asset valuation, bankable project identification, and innovative instruments such as municipal blue bonds and environmental impact bonds to expand fiscal space and support sustainable marine‑based development.